Nocturnal hydration prepares desert cyanobacteria for dawn-light harvesting by inducing phycoerythrin synthesis - Yang Bai; Hai-Feng Xu; Ren-Han Li; Ai-Wei Zuo; Ge-Yan Liu; Chen Yu; Jin Zhang; Ke Liu; Guo-Zheng Dai; Aaron Kaplan; Bao-Sheng Qiu (Proceedings of the National Academy of Sciences, 2026)
As crucial ecosystem engineers in global drylands, desert cyanobacteria regulate biogeochemical cycling and contribute to the stabilization of arid soils. These extremophiles frequently exploit nocturnal dew deposition to resume metabolism, activate photosynthesis during brief dawn illumination, and then return to diurnal quiescence. Although phycobilisome remodeling is a key evolutionary adaptation for light capture under dim conditions, the molecular mechanisms that optimize light harvesting during the narrow window of hydration/light overlap remain unclear. Here, we show that genes involved in phycoerythrin (PE) synthesis are induced primarily by nighttime rehydration, prior to light exposure. We identify SigB1 as an essential regulator of PE synthesis, where it functions in concert with the activator CpeR1. Deletion of sigB1 disrupts PE production, thereby establishing its central role in this pathway. We further identify Hrr1 (hydration-responsive regulator 1) as an upstream transcription factor that is induced following nighttime water uptake and, in turn, activates sigB1 and cpeR1 , thereby initiating transcription of PE biosynthetic genes. Notably, we also find that SigB1 is regulated by the chromatic acclimation factor RcaF, which suppresses PE synthesis as weak dawn light emerges. Together, these findings reveal that nocturnal rehydration triggers an anticipatory transcriptional program that primes PE synthesis, enabling desert cyanobacteria to maximize light harvesting at dawn. More broadly, our results provide insight into how desiccation-tolerant photosynthetic organisms dynamically optimize their light-harvesting apparatus in response to transient environmental cues.